Surgical methods for the correction of erectile dysfunction - P. S. Kyzlasov; A. T. Mustafayev; P. D. Plyasova; A. I. Bokov; A. S. Saidov; E. A. Povelitsa (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Erectile dysfunction, remaining an urgent problem of our time, is pushing the world urological community to develop new methods of diagnosis and treatment. Currently, urologists have in their arsenal a variety of both conservative and surgical methods for correcting erectile dysfunction. This manuscript provides an overview of modern surgical treatment methods based on world literature data.